ANALYSIS OF OPTIMUM USE INWARDLY PRODUCTION RESERVES OF THE BUILDING ENTERPRISE - R. T. Ismailov; V. B. Melehin (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
In article are considered role and problems of the economic analysis, conducted for the reason discovery available besides building enterprise inwardly production reserves. It is offered economic and mathematical model of the optimum distribution inwardly production reserves between simultaneously building object, providing receptions of the maximum profit.